2021
DOI: 10.1021/acs.jpca.1c04056
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solution of Kinetic Analysis for Thermally Activated Delayed Fluorescence Materials

Abstract: The photophysical analysis of thermally activated delayed fluorescence (TADF) materials has become instrumental for providing insights into their stability and performance, which is not only relevant for organic light-emitting diodes but also for other applications such as sensing, imaging, and photocatalysis. Thus, a deeper understanding of the photophysics underpinning the TADF mechanism is required to push materials design further. Previously reported analyses in the literature of the kinetics of the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 42 publications
3
103
0
Order By: Relevance
“…Organic TADF molecules were chosen as listed in Table S12 (ESI†) and their photophysical properties were collected from literature. 13,49,57–77 Although the theoretical methods used to determine values for the NTO overlap were the same as those applied for the coinage metal complexes, different methods used to obtain experimental values for organic TADF molecules make the comparisons problematic. Nevertheless, the theoretical Δ E ST values can still be evaluated as all compounds were calculated using the same method and basis set and show a clear increase with greater NTO overlap (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic TADF molecules were chosen as listed in Table S12 (ESI†) and their photophysical properties were collected from literature. 13,49,57–77 Although the theoretical methods used to determine values for the NTO overlap were the same as those applied for the coinage metal complexes, different methods used to obtain experimental values for organic TADF molecules make the comparisons problematic. Nevertheless, the theoretical Δ E ST values can still be evaluated as all compounds were calculated using the same method and basis set and show a clear increase with greater NTO overlap (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12 Organic TADF materials generally have slow ISC rates (k ISC = 10 5 -10 8 s À1 ) owing to weak spin-orbital coupling (SOC), which makes fluorescent radiative decay k S 1 r À Á competitive with intersystem crossing. 49 Consequently, the radiative decay rate for TADF (k TADF radiative rate of S 1 k S 1 r À Á…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S2, ESI‡), m -CzBNCz 27 and BSBS-N1 , 38 where k RISC reaches 1.08 and 1.90 × 10 6 s −1 , respectively. Even direct comparison between reported RISC rates from different research teams is challenging though, due to the plurality of reported methods for determining its value 39,40 and subtle yet important practical concerns. 41 The MR-TADF emitters with the fastest k RISC are nevertheless two orders of magnitude slower than the best performing D–A TADF emitter (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…S2, ESI ‡), m-CzBNCz 27 and BSBS-N1, 38 where k RISC reaches 1.08 and 1.90 Â 10 6 s À1 , respectively. Even direct comparison between reported RISC rates from different research teams is challenging though, due to the plurality of reported methods for determining its value 39,40 and subtle yet important practical concerns. 41 The MR-TADF emitters with the fastest k RISC are nevertheless two orders of magnitude slower than the best performing D-A TADF emitter (Fig.…”
Section: Introductionmentioning
confidence: 99%